Judicial Review of Rulemaking - Sarro, Douglas (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2025)
Recently, there has been a push for courts to review rules made by the executive for substantive reasonableness. While reasonableness review may foster better-informed regulation, it also risks giving vested interests disproportionate influence over rulemaking. By flooding rulemakers with analyses emphasizing regulation’s costs and uncertainties about its benefits, to which rulemakers must then respond so as to survive reasonableness review, these interests can slow down and frustrate regulation designed to benefit the public. Courts could mitigate this risk, however, by applying reasonableness review in a way that recognizes the uncertainty that attends the rulemaking process—including the limits it imposes on rulemakers’ ability to refute alternative analyses of new rules’ likely costs and benefits. This does not mean acquiescing in arbitrary decision-making. To the extent rules’ effects are uncertain at adoption, courts can encourage rulemakers to revisit these rules post-implementation. Properly designed, reasonableness review can foster informed regulation that responds to new evidence and is less easily diverted from public-oriented objectives.